Optimization of traveling salesman problem with Google app engine project report - Lin, Runhui. (2011)
This report focuses on the design, development and result analysis of final year project ―Optimization of Travelling Salesman Problem with Google App Engine‖. The Travelling Salesman Problem (TSP) is a very useful mathematic problem that could be applied in scientific and industrial activities. However, since there is not a general solution for this kind of problem, looking for a optimal solution of a TSP is difficult and consuming. The aim of this project is to apply the idea and production of cloud computing into generating solutions for TSP as well as provide a user-friendly user interface to potential clients. Google App Engine, being a new cloud-computing product is chosen for this project to perform the solutioning algorithm of TSP. The project experienced some difficulties in the design of data storage and transmission. But, it eventually proved that cloud computing is of great potential in providing TSP solutions.